Asuhan Keperawatan Pada Ny. A Dengan Gastritis Di Ruang Pejuang RSUD Bangkinang Tahun 2024 - Maharul Man; Neneng Fitria Ningsih (Excellent Health Journal, 2025)
Gastritis is inflammation of the stomach lining. This inflammation causes the stomach lining to swell, which ultimately causes the formation of epithelium from the stomach lining. Factors that are at risk for gastritis include smoking habits, a diet high in fat or salt, increasing age because over time the gastric mucosal lining will thin and weaken. The aim of this research is to examine and implement nursing care for patients with gastritis in the Warrior Room at Bangkinang Regional Hospital in 2024. This research method uses a descriptive research design in the form of a case study. The respondent in the case report is Mrs. A is 46 years old with gastritis. Data obtained by interviews, physical examination and supporting examinations. During the assessment the patient said he had pain in the pit of the stomach, nausea, vomiting, his right hand felt numb, his appetite decreased, the patient looked weak and lethargic. So researchers can formulate the main problem with the nursing diagnosis of acute pain related to physiological injurious agents. The intervention provided is identification of location, characteristics, duration, frequency, intensity of pain, and pain scale. In carrying out nursing actions on Mrs. A with gastritis is carried out according to the nursing plan that has been prepared. The results of the four day nursing visit to the client were resolved and plans were maintained. The researcher's hope from writing this case report is that it can provide a reference in providing nursing care to patients with gastritis.